Types and forms of sleeping dens of pacas (Cuniculus paca) in the upper Itaya river basin - Aquino, Rolando (2012)
This report deals with paca sleeping dens (Cuniculus paca Linnaeus, 1766). The study was conducted between August 2006 and April 2007 and is based on detailed observations. Results indicate that this rodent uses holes in the ground or in fallen trees as sleeping dens. Each of these sleeping dens had two or more orifices and an internal cavity for the "diurnal sleep”. Typically, one orifice was for common use and the rest for the circumstantial escape. According to their form, their localization in the ground, and the number and location of orifices, sleeping dens were classified into four types, of which type A was the most common. The results also indicate a greater concentration of sleeping dens in temporary flooded gallery forest.